O externalismo com rosto humano: interpretando a semântica de Hilary Putnam e suas aplicações - Fonseca, Alexandre Müller (2016)
The semantic externalism was a philosophical view, formulated by Hilary Putnam, which claims that classificatory terms of one language depend, for their correct application, on collective endorsement (by the people who use them) and on the environment. Thus, the meaning of a term which designates a specimen or object depends, as a final criteria of decision in case of doubt, on specifications arising from specimen and object themselves. Hence, scientific determinations are fundamental. So, what adequately determines the reference of a term is not determined by the beliefs which an individual has concerning some object; the environment and other persons are the main factors which are the responsible for making what person says consistent with the object designated by the term used. Putnam s formulations have been read as essencialist, because he seems sometimes to say that natural kinds (gold, water etc.) are discriminated based on their intrinsic properties. What matters in semantics are the uses we make of general classificatory terms and as a delegate in the present state of our society, to others, the power to judge and recognize certain objects under which the laity have insufficient or no understanding. That said, it will be seen that externalists applications to specific sciences such as biology and chemistry are fruitless and that its application to the attempted right by some authors to be seen as a way out to solve historical problems of legal philosophy did not overcome the positivist matrix put forth by Herbert Hart. Concluding, I propose that, with the necessary adjustments, semantic externalism is compatible with Hart s semantic approach to law.